Actively controlled plasmonic Bragg reflector based on a graphene parallel-plate waveguide - Yueke Wang (AIP Advances, 2015)
We investigate theoretically and numerically a graphene parallel-plate waveguide structure with two alternate chemical potentials (which can be realized by alternately applying two biased voltages to graphene). A plasmonic Bragg reflector can be formed in infrared range because of the alternate effective refractive indexes of SPPs propagating along graphene sheets. By introducing a defect into the Bragg reflector, and then the defect resonance mode can be formed. Thanks to the tunable permittivity of graphene by bias voltages, the central wavelength and bandwidth of SPPs stop band, and the wavelength of the defect mode can be tuned.